Functionally graded PbTe-based compound for thermoelectric applications - Dashevsky, Z.; Dariel, M.P.; Shusterman, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The present study summarizes a feasibility study of the influence of the graded indium profile that is set up by the diffusion of indium from an external source, on the transport properties of PbTe crystals. PbTe crystals were grown by Czochralski technique. The penetration profiles of indium, diffusing from an external gaseous source was determined using Seebeck coefficient measurements in PbTe doped preliminary by Na impurity. The Seebeck coefficient changed a sign as the indium concentration induced a change from p-type to n-type character. Doping by indium generates deep impurity states lying close to the edge of the conduction band. Electron concentration practically didn't change along PbTe<In> crystal while indium concentration changed from 3·10¹⁹ to 5·10²⁰ cm⁻³. The thermovoltage V of a PbTe crystal in which an In concentration profile had been established was determined up to temperature ≈600 °C (in this case temperature of the cold side was constant ≈50 °C). It was discovered that V increases linearly with increasing temperature difference. This effect is connected with practically constant value of Seebeck's coefficient in a wide temperature range through stabilization (pinning) of Fermi level by producing a concentration gradient of In impurity in PbTe crystals.